THE INFLUENCE OF SOCIAL SUPPORT ON CAREER DECISIONS - Arfan, Arfan; Prayoga, Prayoga (Program Studi Bimbingan dan Konseling FKIP UNJA, 2023)
This study aims to determine the effect of social support on career decisions. With the development of science and technology, people choose professions based on their interests, talents, abilities, motivation to fulfill their daily needs, and motivation to realize themselves. However, before making a career decision, one of the supports is psychological well-being which concerns the condition of individual social support. Someone who has a lot of social support, the lower the psychological problems such as depression, anxiety and stress. On the other hand, when social support is low, psychological problems such as depression, anxiety and stress are greater. Thus affecting the psychological well-being and career decisions of individuals. This study shows that social support has a significant relationship related to psychological well-being and career decisions, the hypothesized results of several relevant articles indicate that a positive value means that if social support increases, then psychological well-being increases which influences individual career decisions.